Impact of 17-alpha ethinyl estradiol (EE2) and diethyl phthalate (DEP) exposure on microRNAs expression and their target genes in differentiated SH-SY5Y cells - Agnese Graziosi; Camilla Corrieri; Giulia Sita; Luca Ghelli; Sabrina Angelini; Roberta d’Emmanuele di Villa Bianca; Emma Mitidieri; Raffaella Sorrentino; Patrizia Hrelia; Fabiana Morroni (Scientific Reports)
Abstract Environmental endocrine disruptor chemicals (EDCs) have raised significant concerns due to their potential adverse effects on human health, particularly on the central nervous system (CNS). This study provides a comparative analysis of the effects of 17-alpha ethinyl estradiol (EE2) and diethyl phthalate (DEP) on neuronal cell proliferation and neurotoxicity. Using differentiated SH-SY5Y human neuronal cells, we evaluated cell viability, microRNA (miRNA) regulation, and RNA expression following exposure to subtoxic concentrations of EE2 and DEP. Our results show that both EDCs downregulated specific miRNAs—miR-18b-5p, miR-200a-3p, and miR-653-5p—affecting key processes such as cell proliferation, survival, and apoptosis. Gene expression analysis revealed the upregulation of EGFR, IGF1R, BTG2, and SH3BP4, implicating these miRNAs in the regulation of the Ras and PI3K/Akt/mTOR pathways. Our findings highlight distinct cellular responses: DEP disrupts PTEN activity, while EE2 enhances phosphorylation within the PI3K/Akt/mTOR pathway, promoting pro-survival and anti-apoptotic signals. This study emphasizes the urgent need for regulatory measures to mitigate the neurotoxic effects of EDCs and offers valuable insights into their molecular impacts on brain health.